Internal vascular channel architecture in human auditory ossicles. Issue 2 (31st March 2022) - Manoharan, Shivani M.; Gray, Roger; Hamilton, John; Mason, Matthew J.
Abstract: The vascular supply of the human auditory ossicles has long been of anatomical and clinical interest. While the external blood supply has been well‐described, there is only limited information available regarding the internal vascular architecture of the ossicles, and there has been little comparison of this between individuals. Based on high‐resolution micro‐CT scans, we made reconstructions of the internal vascular channels and cavities in 12 sets of ossicles from elderly donors. Despite considerable individual variation, a common basic pattern was identified. The presence of channels within the stapes footplate was confirmed. The long process of the incus and neck of the stapes showed signs of bony erosion in all specimens examined. More severe erosion was associated with interruption of some or all of the main internal vascular channels which normally pass down the incudal long process; internal excavation of the proximal process could interrupt vascular channels in ossicles which did not appear to be badly damaged from exterior inspection. An awareness of this possibility may be helpful for surgical procedures that compromise the mucosal blood supply. We also calculated ossicular densities, finding that the malleus tends to be denser than the incus. This is mainly due to a lower proportion of vascular channels and cavities within the malleus. Abstract : The major internal vascular channels and cavities of the human malleus and incus were reconstructed using micro‐computed tomography. Although there was substantial variation between individuals, a common basic pattern was identified. Erosion of the long process of the incus can interrupt internal channels, which could leave this process more vulnerable to surgical insult.